2014
DOI: 10.3892/mmr.2014.1980
|View full text |Cite
|
Sign up to set email alerts
|

BMI-1 is important in bufalin-induced apoptosis of K562 cells

Abstract: Abstract. The purpose of this study was to analyze the effects of bufalin on the gene expression of K562 cells and on the expression of BMI-1 pathway constituents in K562 cell apoptosis. K562 cells were treated with bufalin, and the inhibition rate and apoptosis were detected by an MTT assay, flow cytometry and a microarray assay. BMI-1, p16 INK4a and p14 ARF were examined by quantitative polymerase chain reaction (qPCR). Bufalin induced significant changes in the gene expression of the K562 cells; 4296 genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Bufadienolides are a class of C24 steroids with a distinctive α-pyrone ring at the C17 position, which have attracted a lot of attention due to their excellent medical properties. In nature, they are mostly synthesized by toads and secreted through parotoid glands and cutaneous glands as a defensive weapon. Bufadienolides are well known for their cardiotonic properties, and recently their anticancer activities have also attracted much attention. In vitro cell experiments and in vivo animal models have shown that bufadienolides can effectively inhibit the cell proliferation of many types of tumors. They are the major active ingredients of the Chinese medicine Chansu and Cinobufacini. Now, Cinobufacini is one of the best-selling antitumor Chinese medicine in China.…”
Section: Introductionmentioning
confidence: 99%
“…Bufadienolides are a class of C24 steroids with a distinctive α-pyrone ring at the C17 position, which have attracted a lot of attention due to their excellent medical properties. In nature, they are mostly synthesized by toads and secreted through parotoid glands and cutaneous glands as a defensive weapon. Bufadienolides are well known for their cardiotonic properties, and recently their anticancer activities have also attracted much attention. In vitro cell experiments and in vivo animal models have shown that bufadienolides can effectively inhibit the cell proliferation of many types of tumors. They are the major active ingredients of the Chinese medicine Chansu and Cinobufacini. Now, Cinobufacini is one of the best-selling antitumor Chinese medicine in China.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that Bufalin is a broad-spectrum anti-tumor drug ( 23 ). At present, it has shown its anti-tumor activity in the clinical treatment of leukemia, liver cancer, gastric cancer and other tumors ( 24 , 25 ). A study has found that Bufalin can inhibit the proliferation of vascular endothelial cells in a variety of tumor tissues, affect its neovascularization, and then inhibit tumor growth ( 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…A study has found that Bufalin can inhibit the proliferation of vascular endothelial cells in a variety of tumor tissues, affect its neovascularization, and then inhibit tumor growth ( 26 ). In leukemia-related study, it was found that Bufalin could significantly inhibit the growth of leukemic cells and induce their differentiation and apoptosis ( 25 ). Studies have shown that Bufalin can activate members of Caspase family and Bcl-2 family, promote the formation of Bax homodimer ( 27 ), and activate hydrolases such as Caspase-8, Caspase-9 and Caspase-3, which significantly increase the permeability of mitochondrial membrane and lead to the release of cytochrome C into the cytoplasm.…”
Section: Introductionmentioning
confidence: 99%